Sosialisasi dan Pendampingan Penerapan Pembelajaran Mendalam bagi Guru-Guru Matematika SMP di Lumajang - Didik Sugeng Pambudi; Frenza Fairuz Firmansyah; Dwi Purwanti; Muhammad Safak; Sochif Prasetiya (Perkumpulan Kualitama Edukatika Indonesia, 2026)
Deep Learning is recommended by the Ministry of Primary and Secondary Education for implementation in the learning process at schools. This community service activity aimed to provide information and guidance on the implementation of Deep Learning to junior high school mathematics teachers at the Lumajang Mathematics Teachers’ Working Group (MGMP). The activity was conducted on 9 October 2025 with 52 mathematics teachers at the Lumajang Junior High School Mathematics Teachers’ Working Group (MGMP). The methods used included information sharing, discussion, teaching practice, observation, and the distribution of questionnaires. The results of the activity were very positive, with all participants understanding the three main principles of Deep Learning, namely (1) Mindful Learning, (2) Meaningful Learning, and (3) Joyful Learning. Each group of teachers produced a lesson plan for a mathematics lesson in Junior High School. From the results of teaching demo in the classroom, some of participants were found to be able to apply the Deep Learning approach effectively. This was evident from (1) teachers explaining the material using video that captured the students’ interest, (2) teachers applying the three main principles of Deep Learning effectively, (3) students actively participating in group discussions and presenting the results of these discussions in front of the class, and (4) students understanding the material well. The questionnaire results showed that all teachers stated that such mentoring activities need to be continued in order to enhance teachers’ professionalism.